Analisis Strategi dan Taktik Pemasaran dalam Aktivitas E-Commerce untuk Meningkatkan Pertumbuhan PT Golden Rama Express - Annetta Gunawan (Bina Nusantara University, 2014)
Opportunities for tour & travel industry in Indonesia is increasing, thus attracting a lot of players to compete. PT Golden Rama Express as an industry leader in the tour industry wants to continue to grow the business. The development of information technology led to changes in consumer behavior, encouraging Golden Rama to take advantage of gaps that occur to become a leader in e-commerce activities. The purpose of this project consulting is to devise marketing strategies and tactics in order to improve the effectiveness of e-commerce activity for the Golden Rama. This study used questionnaire, interview, and literature study as a means to collect the data. Then the results of the data analysis of both quantitative and qualitative were used to plan growth based on the concept of Matrix Nine. The results of this study revealed that the existing customers of PT Golden Rama Express which can be expanded to the e-commerce market are upper middle families who have often gone abroad. Wife has significant role in filtering and selecting information and its potential customers are families who are beginners in terms of holidaying abroad are active in the virtual world with the characteristics as early adopters. This study is expected to be input to the PT Golden Rama Express in determining marketing strategies are needed in the market work is done by integrating the activities of online, offline, and mobile, based on the concept communitization, confirmation, and the clarification, which is equipped with the concept of Crossing the Chasm. Then the marketing tactics is based on the concept of communal activation and conversation, improve Web site content, as well as applying the principle of contextual marketing.